On Interaction or Methods of Scientific Cognition of Society - Morkūnas, Zigmas (Problemos, 1970)
The paper shows that apparent technological and social conditions for universal requirements provide ground for their scientific analysis. This is so because production in sufficiency is overcome and because of the direct appropriation of nature as a means of production, on the one hand, and as the individual appropriation of objects of consumption, on the other hand. The analysis in question helps to expose a concrete stage of transition into classless society. It helps to determine the degree of presence of these conditions, to lay bare the subject and means and use them practically in order to speed up the creation of these conditions. Correctness of a theory is corroborated by practical realisation of the direct collective appropriation of nature of by creating homogeneous communist relations of production, since they guarantee desirable effects both for society and its members.